2016
DOI: 10.1097/ta.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of platelet function is common following even minor injury

Abstract: Prognostic/epidemiogic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 19 publications
4
46
0
Order By: Relevance
“…Finally, Sirajuddin et al recently reported on the apparent ubiquity of platelet dysfunction in a cohort of 459 minimally injured trauma patients (median ISS 5 5). 49 Patients in their study had lower platelet inhibition to ADP and AA stimulation (58% and 30%, respectively) than patients in other studies presenting with hemorrhagic shock (97% and 50%, respectively) 50 or severe TBI (87% and 38%, respectively), 51 but nevertheless had significant platelet inhibition compared with uninjured controls. How should these data be interpreted?…”
Section: Platelet Dysfunctionmentioning
confidence: 66%
See 1 more Smart Citation
“…Finally, Sirajuddin et al recently reported on the apparent ubiquity of platelet dysfunction in a cohort of 459 minimally injured trauma patients (median ISS 5 5). 49 Patients in their study had lower platelet inhibition to ADP and AA stimulation (58% and 30%, respectively) than patients in other studies presenting with hemorrhagic shock (97% and 50%, respectively) 50 or severe TBI (87% and 38%, respectively), 51 but nevertheless had significant platelet inhibition compared with uninjured controls. How should these data be interpreted?…”
Section: Platelet Dysfunctionmentioning
confidence: 66%
“…The specific mechanism is unknown but may involve "platelet exhaustion," where platelets become activated en masse and are refractory to further stimulation for up to 24 hours afterward. 52,53 However, because the minimally injured patients above 49 had little evidence of bleeding (2% mortality and minimal transfusion requirements [Babak Sarani, George Washington University, electronic communication, May 17, 2016]) despite inhibition of platelet function on TEG-PM, the contribution of such platelet dysfunction to TIC is ambiguous. A recent study by Stalker et al investigating location-dependent differential platelet activation and organization may shine some light on this question.…”
Section: Platelet Dysfunctionmentioning
confidence: 99%
“…Given their critical roles in hemostasis and inflammation, platelets are a logical cellular target for investigation as a link between the excessive inflammatory response after injury and the regulation of thrombosis. The degree of platelet dysfunction following trauma is profound, with some reports suggesting that up to 45% of patients on admission and 90% of patients in the intensive care unit after trauma have impaired response to platelet agonists (39), with even minimally injured patients manifesting with some dysfunction(40). Importantly, impaired response to platelet agonists has been linked to mortality following trauma(41).…”
Section: Pro: Coagulopathy Should Be a Therapeutic Target In Criticalmentioning
confidence: 99%
“…Specifically, trauma patients maintain their dense granules even in the presence of ADP receptor inhibition contradicting the theory of platelet granule exhaustion as the etiology for platelet dysfunction [12]. Furthermore, other studies have documented a significant inhibited response to ADP following minor trauma, suggesting receptor status may be a biomarker of injury rather than a mediator of TIC [13]. Therefore, we propose to assess the role of platelet ADP receptor dysfunction, measured by TEG –PM mapping in predicting mortality, requirement of massive transfusion and platelet transfusion among patients at risk for TIC.…”
Section: Introductionmentioning
confidence: 99%